Dairy producer perceptions toward male dairy calves in the Midwestern United States - Creutzinger, Katherine C.; Pempek, Jessica A.; Locke, Samantha R.; Renaud, David L.; Proudfoot, Kathryn L.; George, Kelly; Wilson, Devon J.; Habing, Greg (Frontiers in Animal Science, 2022)
Male dairy calves are often sold from the farm of birth within the first few days of life. Research describing the care of male calves is limited, with emphasis on parsing differences between the care of male and female calves. The aims of this study were to describe dairy producers’ self-reported care practices for male relative to female calves, as well as their perceptions toward male calf care and welfare. Overall, 24 dairy producers in Ohio and Indiana participated in 1 in-person focus group (n = 10) or were individually interviewed (n = 14) using a semi-structured questionnaire with closed and open-ended questions about neonatal calf care. Discussions were audio recorded and transcribed verbatim. Data from closed-ended questions are described quantitatively, and thematic analysis was used to identify common themes discussed by producers for open-ended questions. A majority of producers described using different care protocols for male and female dairy calves (64%; 9/14 interview participants). Low input care practices were more commonly consistent between male and female calves, such as colostrum protocols (71%; 10/14 interview participants) and navel care (100%; 14/14 interview participants) than more costly treatments. Of the producers that provided disease prevention products to female calves (79%; 11/14 interview participants), only a few also administered them to male calves (27%; 3/11 interview participants). Three major themes were constructed from the open-ended questions, including factors affecting male dairy calf care, attitude toward male calf welfare, and opportunities to improve male dairy calf welfare. Producers described multiple factors that influenced male calf care on the dairy, such as time and money required to care for them. There was divergence in concern among producers about male calf welfare, with some producers expressing concern, particularly for calves slaughtered soon after birth; yet others described feelings of indifference about the topic. Potential ways to improve male calf welfare, including greater sale prices and the involvement in specialized marketing schemes, were suggested by some producers. These findings highlight potential concerns for male calf welfare and ways to improve future care on dairy farms.